KEMAMPUAN MENULIS AYAT AL- QUR’AN SISWA MAN PALOPO - Muhammad Agil Amin (Asosiasi Dosen Muda Indonesia, 2022)
This article discusses the ability to write verses of the Qur'an for MAN Palopo students. This type of research is education and development, Research & Development (R&D). The subjects of this study were 29 students of MAN Palopo. Data collection techniques in this study consisted of observation, questionnaires, tests and documentation. The results of the study show that the resulting teaching materials are feasible to use. Feasibility indicators meet valid and effective standards. The validity score based on the expert validator's assessment generally obtained a value of 0.67 (Valid), which can be used in learning. Effectiveness based on the N-gain test obtained a value of 0.52 included in the medium category with an increase in the pre-test score of 67.03 to the post-test value of 84.17.